Interpreting West Ashcom: Drones, Artifacts, and Archives - Gijanto, Liza (International journal of historical archaeology, 2020)
Archaeology from St. Mary’s College of Maryland began looking for the former homestead of West Ashcom in the Spring of 2012. West Ashcom was established on the south bank of the Patuxent River in what is now St. Mary’s County, MD by John Ashcom in 1651. At its height in the early eighteenth century it contained a manor house, kitchen, dairy, orchard, port, haberdashery, and various other barns and dependencies. Using traditional sources such as archives and methods like pedestrian surveys and surface collections, a late seventeenth/early eighteenth-century site was identified in a plowed field. Since then, archaeologists from SMCM have employed a range of sources, field methods, and mapping techniques to define the parameters of the site, past structures, and identify activity areas in a largely compromised area. This paper summarizes the results of more traditional uses of GIS mapping paired with experimental drone data to demonstrate the benefit of mixing old and new technologies when interpreting sites subject to continuous plowing and planting.